2012
DOI: 10.3329/cardio.v5i1.12205
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Impact of Percutaneous Transvenous Mitral Valve Commissurotomy (PTMC) on Right Ventricular Function

Abstract: Background: The aim of this study was to evaluate the immediate impact of Percutaneous Transvenous Mitral Commissurotomy (PTMC) on RV function in patients with mitral stenosis (MS).Methods: This study was conducted in the National Institute Cardiovascular Diseases, Dhaka for a period of one year starting from October 2008 to September 2009. A total of 50 consecutive patients (Case group) with mitral stenosis were selected after considering inclusion and exclusion criteria that subsequently undergone PTMC. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…These parameters are consistent with other studies done by Drighil et al (2008) and Borges et al (2006) and Kundu et al (2012).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These parameters are consistent with other studies done by Drighil et al (2008) and Borges et al (2006) and Kundu et al (2012).…”
Section: Discussionsupporting
confidence: 83%
“…Right ventricular dysfunction is likely as important as tricuspid regurgitation because it offers an explanation for the negative prognostic The quantitative echocardiographic assessment of RV function is difficult because of the ventricle's complex The mode of clinical presentation in this study shows, 90% patients complained of fatigue, shortness of breath in 85%, palpitation in 65%, chest pain in 28%, ankle edema in 15%, headache among 10% and dizziness in 25%. Another study Kundu et al (2012) reported that the majority (80%) of the patients complained shortness of breath, followed by 64% with palpitation, 30% with cough, 24% with chest pain and 6% with hemoptysis which is consistent with our current study.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Post PTMC pulmonary artery systolic pressure, though found reduced significantly, still higher than that found in other studies. 26,27 In this study net atrioventricular compliance increased from 3.42 ± 1.64 to 6.38 ± 7.36 ml/ mm of Hg. Aditya Kapoor et al 25 found that left atrial compliance significantly improved immediately after successful balloon mitral valvotomy, irrespective of the pre valvotomy left atrial pressure.…”
Section: Resultsmentioning
confidence: 85%
“…the study conducted by Drighil et al 8 showed reduction of PASP from 46.4 ± 32.1 mmHg to 29.1 ± 13.4 mmHg ( P = 0.02). Kundu 30 et al showed reduction from 47.7 ± 7.9 to 28.2 ± 5.9 (p<0.001). Similar results were also seen in other studies conducted by Mohan JC et.al.…”
Section: Paspmentioning
confidence: 99%